Dosage de quelques micropolluants organiques dans les eaux brutes par HPLC - KHAOULA HEZAIMIA; KHAOULA SIAD (My University, 2022)
Water is becoming a rare commodity, especially with climate change and its increasing pollution, which threatens the existence of several plant and animal species. In the light of this observation, we considered it useful to measure some organic micro pollutants in the raw water by UV-vis, IR and HPLC. We have chosen four pesticides, namely (AKTARA, ZOOM, COSSACK and TRAXOS ONE) as organic micro pollutants for our study. The physico-chemical results of our raw water sample showed that for the values of temperature 15.5°C and pH=8.29; nitrates = 9.768 mg/l; the sulfates = 19.875 are within the standards, however the turbidity = 56.05 mg/l; BOD5= 214 mg/l; chlorides= 44.9 mg/l are out of the ordinary. UV-Vis to show that pesticides absorb with a wavelength λ= 252 nm for AKTARA. λ= 202 nm for ZOOM; λ= 190 nm for COSSACK; λ =199 nm TRAXPS ONE The results obtained from the various chromatograms of the pesticides studied and from the raw water by HPLC show the presence of pesticide in the form of a trace, with Tr of 6 min and 8.5 min with a low intensity and using the results obtained from from UV-Vis and IR we can deduce that our raw water contains traces of AKTARA and COSSACK pesticides. These results show that our raw water contains pesticides in trace form and which can present a real danger as long as this water is used to irrigate the neighboring wheat fields. --------------------------------------------------------------------------------------------------- أصبحت المياه سلعة نادرة خاصة مع تغير المناخ وتزايد تلوثه الذي يهدد وجود العديد من األنواع النباتية والحيوانية. في ضوء هذه المالحظة ، اعتبرنا أنه من المفيد قياس بعض الملوثات العضوية الدقيقة في المياه الخام بواسطة األشعة فوق .HPLC البنفسجية ، واألشعة تحت الحمراء ، و كملوثات عضوية (ONE TRAXOS و COSSACK و ZOOM و AKTARA ( لقد اخترنا أربعة مبيدات حشرية ، وهي دقيقة لدراستنا. أظهرت النتائج الفيزيائية والكيميائية لعينة الماء الخام أنه بالنسبة لقيم درجة الحرارة 5.15 درجة مئوية ودرجة الحموضة 29.8 = ؛ النترات = 768.9 ملغم / لتر ؛ الكبريتات = 875.19 ضمن المعايير ، لكن العكارة = 05.56 ملجم / لتر ؛ . ملغم / لتر ؛ الكلوريدات = 9.44 مجم / لتر خارج عن المعايير 214 = BOD5 الظهار أن مبيدات الافات أكتارا = 252 نانو ماتر زوم = 202 نانو ماتر كوزاك = 190 نانو ماتر تركسوسوان = 199 نانو ماتر HPLC النتائج التي تم الحصول عليها من المخططات الكروماتوجرافية المختلفة للمبيدات المدروسة ومن المياه الخام = بواسطة تبلغ 6 دقائق و 5.8 دقيقة بكثافة منخفضة وباستخدام النتائج التي تم الحصول Tr ، تظهر وجود مبيد حشري على شكل أثر مع و AKTARA يمكننا أن نستنتج أن مياهنا الخام تحتوي على آثار لمبيدات الآفات IR و Vis - عليها من الأشعة فوق البنفسجية COSSACK. تظهر هذه النتائج أن مياهنا الخام تحتوي على مبيدات حشرية في صورة أثرية والتي يمكن أن تشكل خط را حقيقيًا طالما يتم استخدام هذه المياه لري حقول القمح المجاورة. ------------------------------------------------------------------------------------------- L’eau devient une denrée rare surtout avec les changements climatique et sa pollution croissante qui menace l’existence de plusieurs espèces végétale et animale. A la lumière de ce constat, nous avons jugé utile de doser quelques micro polluants organique dans l’eau brute par UV-vis , IR et l’HPLC Nous avons choisis quatre pesticides à savoir ( AKTARA , ZOOM ,COSSACK et TRAXOS ONE) en qualité de micro polluants organique pour notre étude Les résultats physico chimique de notre échantillon d’eau brute ont montrés que pour les valeurs de Température 15.5°C et le pH=8.29 ; les nitrates = 9.768 mg/l ; les sulfate = 19.875 sont dans les normes par contre la turbidité =56.05 mg/l ; la DBO5= 214 mg/l ; les chlorures= 44.9 mg/l sont hors norme . L’UV—Vis à montrer que les pesticides absorbent avec une longueur d’onde λ= 252 nm pour AKTARA . λ= 202 nm pour ZOOM ; λ= 190 nm pour COSSACK ; λ =199 nm pour traxos one Les résultats obtenus à partir des différents chromatogrammes des pesticides étudiées et de l’eau brute par HPLC , montrent la présence de pesticide sous forme de trace , avec Tr de 6min et 8.5 min avec une intensité faible et en faisant appel aux résultats obtenus à partir de l’UV-Vis et L’IR nous pouvons déduire que notre eau brute contient des traces de pesticide AKTARA et COSSACK. Ces résultats montrent que notre eau brute renferme des pesticides sous forme de trace et qui peuvent présenter un réel danger du tant que cette eau sert à l’irrigation des champs de Blé limitrophe .